Quantifying selective pulsed laser cleaning and residual contamination in paper artifacts by ATR spectroscopy - Boynukara, Canan Yagmur; Graziani, Valerio; Uguryol, Mehmet; Mavili, Gurcan; Tortora, Luca; Ruediger, Andreas; Antici, Patrizio (SPRINGER HEIDELBERG, 2026)
Pulsed laser cleaning of cultural heritage materials requires removing unwanted deposits from fragile substrates without inducing collateral damage. This study explores femtosecond (fs) laser cleaning of cellulose-based historical papers through a combined experimental and modeling approach. Paper samples, prepared with traditional Turkish-Ottoman sizings (alum-egg, corn starch, wheat starch) and subjected to artificial aging, were contaminated with graphite and graphite-kaolinite mixtures to replicate historical soiling. Fs laser treatments were performed within the experimentally verified safe fluence range of 0.39-0.78 J/cm2, and the cleaning effects were monitored using Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) spectroscopy. The measurements demonstrated effective removal of graphite and partial reduction of kaolinite, while confirming the preservation of cellulose and sizing features. Burnished samples exhibited lower cleaning efficiency due to deeper contaminant embedding. Beyond these experiments, we introduce, for the first time in the context of paper conservation, the integration of ATR-FTIR spectroscopy with exponential saturation and decay models. This approach enables a quantitative assessment of both cleaning efficiency and residual contamination while providing predictive insight into fluence thresholds extending beyond the experimentally tested range. Overall, the combined experimental-modeling methodology establishes a robust framework for defining safe and effective fs laser cleaning parameters, offering new opportunities for the quantitative optimization of paper artifact conservation.
Keywords: Femtosecond laser cleaning; Paper artifacts; ATR-FTIR spectroscopy; Exponential saturation/decay modeling; Materials Science; Physics